Modelling the Rabies Transmission Dynamics and Control in Sarawak - Nur Asheila, Abdul Taib (UNIMAS, 2023)
In July 2017, the historically rabies-free Sarawak notified its first-ever case of rabies involving two children from the Serian district. As of 2022, rabies is still ongoing in Sarawak and all of the human cases have been classified as dog-mediated rabies. However, modelling studies of rabies in Sarawak are still scarce despite the evolving epidemic in the state. Hence, this research aims to fill the research gap by developing the first mathematical model for the transmission dynamics of rabies among the human population and dog population in Malaysia, in particular Sarawak, and further explore the long-term trend of the disease. By employing the Next Generation Matrix approach, this study will also be the first to determine and estimate the effective reproduction number of rabies in Sarawak. Other objective includes identifying the most influential parameters in the disease dynamics by performing local sensitivity analysis on the model parameters. In this study, data on human rabies in Sarawak were mainly collected from the official online press statement made by the Director-General of Health Malaysia, which include information such as bite cases, number of confirmed cases, post-exposure prophylaxis treatment, and rabies onset date. We have formulated a deterministic, compartmental Susceptible-Exposed-Infected-Vaccinated (SEIV) model that incorporates the dynamics of dog-to-dog and dog-to-human rabies transmission in Sarawak. To scale it to a local context, this model considers the intervention measures conducted by the Sarawak State Health Department and the Department of Veterinary Services Sarawak. In a long run, the model has predicted that the rabies cases in Sarawak would continue to decline, before experiencing a slight bump after 100 months from the initial outbreak in July 2017. Whereas the effective reproduction number for Sarawak rabies is estimated to be 3.06, further model analysis have shown that the disease-free equilibrium point is generally stable and this result has enabled us to ascertain that Sarawak can be rabies-free. Consequently, we have estimated the value of the herd immunity threshold to be 0.67. Thus, approximately 70% of the dog population in Sarawak should be vaccinated annually in order to achieve herd immunity. Apart from intensifying the mass dog vaccination campaigns, mobile vaccine units can be deployed to increase vaccination coverage, while oral rabies vaccination can be an alternative for the free-roaming dog population. Also, our sensitivity analysis revealed the significance of dog population management as a mainstay in any rabies control programmes. In conclusion, towards achieving the goal of zero dog-mediated rabies deaths by 2030, the Sarawak authorities should strengthen their efforts in reducing the dog population through the implementation of humane interventions such as the Trap-Neuter-Vaccinate-Relocate (TNVR) method, targeted removal of strays, chemical sterilisation and surgical sterilisation for dogs.